Session password Blum–Goldwasser cryptography based user three layer authentication for secured financial transaction - Ruba, N.; Khadir, A. S. A. (The Scientific Temper, 2024)
Cloud computing is an eminent and evolving technology that offers various services such as data transaction, authentication, distribution and so on. In this article, session password Blum–Goldwasser Cryptography based user authentication (SPBGCUA) method is proposed to enhance the communication security of cloud services with minimum overhead. Moreover, SPBGCUA is a cryptographic technique that provides secured authentication mechanism for financial transaction with higher confidentiality rate. In order to fill the security lack of recent authentication techniques, this method develops dynamic security structure with key generation, encryption, authentication and decryption techniques. Finally, analysis is performed using SPBGCUA Method on factors such as authentication accuracy, data confidentiality rate and data integrity for number of financial data and cloud users.